Comparison of antenatal care and pregnancy outcome pregnant women diagnosed with fetal death between the COVID-19 pandemic period and pre-pandemic period (Annals of Medical Research, 2022)
Aim: To reveal the preventable complications related to fetal loss more clearly by hypothesizing that the negative effects of the pandemic on antenatal follow-up and daily habits in pregnancies resulting in fetal loss may increase compared to the pre-pandemic period.Materials and Methods: In this question-based study, 80 pregnant women who were diagnosed with fetal death during the pre-pandemic period(September 1, 2019- February 28, 2020) were compared with 80 pregnant women diagnosed with fetal death during the pandemic period (March 1,2020-September 1,2020). Antenatal screening tests, dietary, exercise, smoking, medications, low-income status, fetal anomalies, coexisting medical disorders and, adverse outcomes have been comparatively analyzed between the groups. Results: There was no statistical difference between the periods in terms of the number of antenatal visits (p =0.52). However dietary modification and physical exercise rates were lower during the pandemic (p=0.03, and p0.05). Conclusion: In particular, we demonstrated that the pandemic process negatively affected the daily routine such as physical exercise and dietary in women diagnosed with fetal loss. However, we found the stillbirth rates similar between the periods.
Keywords: Antenatal care; COVID-19; Fetal death; Pregnancy; SARS-CoV-2; Stillbirth